Identifikasi Risiko Bahaya Pada Proses Produksi Batu Alam Di Stasiun Pemotongan Menggunakan Metode Hirarc Dan Five Why's - Dicky Tri Sandyayuda; Widya Setiafindari (Jurnal Kendali Teknik dan Sains, 2023)
PBA Surya Alam is one of the industries engaged in the natural stone processing industry (PBA) which has a fairly high risk of work accidents due to the lack of hazard control in the production process for workers. The application of occupational safety and health at PBA Surya Alam has been implemented, but its application has not been maximized, such as in terms of worker awareness in using personal protective equipment (PPE). From 2020 the cutting station experienced 7 work accident cases, in 2021 the cutting station experienced 4 work accident cases, and in 2022 the cutting station experienced 2 work accident cases. The purpose of this study was to determine the potential for work accidents, risk assessment, and efforts to control hazard risks in natural stone production process activities. In addition, this study aims to determine the most dominant risk controls and provide suggestions for controlling work accident factors in the natural stone production process. Therefore, this study uses the HIRARC (Hazard Identification Risk Assessment and Risk Control) method, which is a method for determining potential hazards that occur, knowing risk assessment to determine risk levels and knowing risk controls to reduce the occurrence of work accidents. The results of calculations using the HIRARC and 5W + 1 H methods show that there are 6 cases of potential hazards recorded at PBA Surya Alam with each risk, namely 6 cases of potential hazards with extreme risk, then as many as 8 potential cases hazard with high risk (high risk), as many as 5 cases of potential hazard with high risk. Whereas for the 5 W + 1 H method in the process of cutting Natural Stone from the results of observations and observations in the field making control proposals such as installing SOP signs at Natural Stone production stations so as a reminder when operators are working, safety controls for employees and safety helmets to minimize falling products (PPE), and controlling the use of gloves.